LARGE B CELL LYMPHOMA-YEAR BY YEAR - Syed, Abdus Samad; Samad, Fauzia Abdus; Rahman, Mahmood ur (Journal of Ayub Medical College Abbottabad, 2007)
Non Hodgkin's Lymphoma (NHL) comprises a group of lymphoproliferative disorders the frequency of which continues to rise. Although many classification systems exist for identifying specific histological subtypes, NHL is generally divided into indolent (low-grade) and aggressive (intermediate- and high-grade) forms. Large B Cell Lymphoma (LBCL) is one of the commonest aggressive NHLs. The aim of this review is to provide a general overview of NHL, its clinically practicable cellular classification, epidemiology and in depth overview of the evolution of treatment of LBCL during the past 5 years. Current guidelines from National Cancer Institute (NCI), USA and National Institute on Clinical Excellence (NICE), UK are mentioned and recommendations according to our own set-up are suggested. Keywords: Non-Hodgkin's Lymphoma, Large B Cell Lymphoma, Rituximab